24. ASSESSMENT OF THE RESULTS OF LAPAROSCOPIC SURGERY FOR RECTAL CANCER IN THAI BINH PROVINCE'S GENERAL HOSPITAL (Vietnam Journal of Community Medicine, 2023)
Background: Laparoscopic surgery to treat rectal cancer has been indicated at Thai Binh ProvincialGeneral Hospital In recent years. The study evaluated the outcome of this surgery.Methods: A cross-sectional descriptive study, 59 rectal cancer patients had laparoscopic surgeryat Thai Binh Provincial General Hospital from January 2019 to June 2021. Record data on age,sex, tumor characteristics, cancer stage, operation time, complications and surgical complications;Survival rate, recurrence rate, survival time and quality of life after surgery.Results: 59 rectal cancer patients had laparoscopic surgery. The mean age was 65.7 years old. Male44.1% and female 55.9%. Hight 35.6%; Middle 30.5% and 33.9%. Stage I, II and III are equivalentto 3.4; 22.0% and 74.6%. 100% patients are carcinoma. Rectal amputation 28.8%; anal sphincterpreservation 71.2%. 100% colorectal anastomosis by stapler. The average surgery time was 199.3minutes. complication rate was 1.7%; Fistula anastomosis 3.3%. The mean follow-up time aftersurgery was 17.8 months. The average number of bowel movements 1 year after surgery was 2.6times. Decrease and loss of sexual function 45.5%. 78.0% good urinary function. The function of analautonomy according to Kirwan standards I, II and III are equivalent 65.9; 24.4 and 9.8%. Recurrence6,8%. The survival rate is 94.9%. Overall and disease-free survival was 30.1 and 32.5 months.Conclusion: Laparoscopic of rectal cancer at Thai Binh Provincial General Hospital is a safe methodwith good results.
Keywords: Rectal cancer, laparoscopic surgery.